Optimization of Religious Coping to Overcome Parental Burnout in Assisting Children to Learn from Home due to the Covid-19 Pandemic - Rencan Carisma Marbun; Rudy Aldri Alouw; Esti Marlina Sirait; Sandy Ariawan (Budapest International Research and Critics University, 2022)
In this pandemic era, parents are faced with the demands of tasks or work accompanying children in learning in addition to other tasks, but on the other hand, parents' abilities are limited. All of this circumstances caused burnout syndrome, which occured in emotional, mental and physical fatigue, cynical and decreased achievement of parents in the task of being an educator and mentoring for children. This study aims to formulate an effective form of religious coping to overcome parental burnout. Religious coping means an individual's attempt to use his or her religious beliefs to prevent or alleviate the psychological impact of the pressures faced. The method used in this study is qualitative descriptive. Some informants admitted that it was difficult when it came to dual functioning, as parents and teachers at home. From the result of the research, it can be conluded that coping strategies, consists of belief in God's omnipotence, praying and believing and committing to God's promise in His Word are very effective at preventing and inhibiting the development of burnout syndrome.